2023
DOI: 10.3390/ijms241210081
|View full text |Cite
|
Sign up to set email alerts
|

Catalase Activity of IgGs of Patients Infected with SARS-CoV-2

Anna S. Tolmacheva,
Margarita K. Onvumere,
Sergey E. Sedykh
et al.

Abstract: Coronavirus disease (COVID-19), caused by the SARS-CoV-2 coronavirus, leads to various manifestations of the post-COVID syndrome, including diabetes, heart and kidney disease, thrombosis, neurological and autoimmune diseases and, therefore, remains, so far, a significant public health problem. In addition, SARS-CoV-2 infection can lead to the hyperproduction of reactive oxygen species (ROS), causing adverse effects on oxygen transfer efficiency, iron homeostasis, and erythrocytes deformation, contributing to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
(108 reference statements)
0
0
0
Order By: Relevance
“…The further analysis of blood samples from recovered COVID-19 patients and individuals vaccinated with Sputnik V showed that COVID-19 survivors had the highest catalase activity in their blood IgGs compared to vaccinated individuals and healthy donors. This suggests that COVID-19 infection may lead to the generation of antibodies with increased catalase activity, potentially posing risks with elevated hydrogen peroxide breakdown [ 147 ].…”
Section: Role Of Catalase In Different Diseasesmentioning
confidence: 99%
“…The further analysis of blood samples from recovered COVID-19 patients and individuals vaccinated with Sputnik V showed that COVID-19 survivors had the highest catalase activity in their blood IgGs compared to vaccinated individuals and healthy donors. This suggests that COVID-19 infection may lead to the generation of antibodies with increased catalase activity, potentially posing risks with elevated hydrogen peroxide breakdown [ 147 ].…”
Section: Role Of Catalase In Different Diseasesmentioning
confidence: 99%